The paper house - Peterson, Lois J., 1952- (Orca young reader., 2012)
"Life is hard for ten-year-old Safiyah in the Kibera slum outside Nairobi. Too poor to go to school, she makes a meager living for herself and her grandmother by selling things she finds at the garbage dump. The pages of the glossy magazines she finds at the dump are full of pictures of beautiful people doing things Safiyah can only dream about. But the magazines also inspire Safiyah to create something that may give her and Cucu the chance of a better life"--P. [4] of cover.